Stillbirth in Twins, Exploring the Optimal Gestational Age for Delivery. Issue 1 (January 2015) - Wood, S.; Tang, S.; Ross, S.; Sauve, R.
<x xml:space="preserve">Abstract</x> ABSTRACT The optimal length of gestation in twin pregnancies is uncertain, but recommendations are to deliver twin fetuses when they reach term. If only 1 twin is affected by preterm stillbirth, delivery may be delayed until term to benefit the surviving fetus. This retrospective cohort study was performed to investigate the relationship between gestational age and stillbirth in twins and to estimate an optimal gestational age for delivery. Data (1992–2007) were obtained from the Alberta Perinatal Health Project, which defines stillbirth as death in utero at 20 weeks' gestation or greater or with a birth weight of 500 g or more and neonatal death as that after live birth up to 28 days of age. The population included all twin pregnancies with fetuses surviving until 23 weeks' gestation or greater. Demographic characteristics, pregnancy complications, mode of delivery, pregnancy outcome, and potential confounding factors were assessed. The primary outcome was stillbirth at 23 weeks' gestation or greater. The impact of using gestational age at delivery compared with gestational age at diagnosis was determined. Of 623, 688 births, 18, 840 were multiple births. Of 323 antepartum stillbirths, 113 had a difference of 1 week or more between gestational age at diagnosis of stillbirth and that at delivery, including 31 of 60 stillbirths delivered at 37 weeks or greater. The final study sample included 17, 724 twin births, of which 236 and 26 were antepartum and intrapartum stillbirths, respectively, and 244 were neonatal deaths. The crude stillbirth rate among twins was 14.8/1000. Of the 202 antepartum stillbirths without congenital anomaly, 83 (41%) involved both twins. Using gestational age at delivery, the risk peak was 22.1/1000 at 40 weeks. Using the best estimate of gestational age at stillbirth, the risk peaked at 7.4/1000 at 38 weeks. Thirty-eight (19%) of the antepartum stillbirths occurred in monoamniotic monochorionic twins, 88 (44%) in monochorionic diamniotic twins, and 57 (28%) in dichorionic diamniotic twins. All stillbirths in monochorionic monoamniotic twins occurred at less than 34 weeks, with most at less than 28 weeks. In monochorionic diamniotic twins, most stillbirths occurred at less than 29 weeks, and the risk increased again at more than 36 weeks. Of 25 stillbirths at 37 weeks or more, 9, 14, and 2 were dichorionic, monochorionic diamniotic, and of unknown chorionicity, respectively. On univariate analysis, preexisting diabetes, small for gestational age (SGA), and a birth weight discrepancy of greater than 20% were significantly associated with stillbirth. Maternal smoking, preexisting hypertension, maternal age 35 years or older, and obesity were not significant risk factors. On multivariate analysis, only SGA and birth weight discrepancy remained significantly associated with stillbirth. Of 26 intrapartum stillbirths, 14 occurred at 23 weeks' gestation. The other intrapartum stillbirths resulted from lethal anomaly (n = 5), asphyxia or trauma (n = 2), infection (n = 1), twin-to-twin transfusion (n = 1), and conditions of immaturity (n = 3). There were 244 neonatal deaths, for a rate of 14.0/1000 live births; 52% were dichorionic twins. Most of the deaths resulted from prematurity and occurred at 23 to 28 weeks. In births with 1 fetus or more with SGA or birth weight discrepancy, at 38 weeks the risk of antepartum stillbirth peaked at 8.3/1000 compared with 6.2/1000 in normally grown twins. At 36 and 37 weeks, risks were 0.7/1000 and 1.0/1000 in the SGA/birth discrepancy group versus 0.5/1000 and 0.8/1000 in the normally grown group. Of the 25 stillbirths that occurred at 37 weeks' gestation or more, 4 of 9 dichorionic twins and 9 of 14 monochorionic twins were normally grown. The stillbirth rate per gestational week was low. Neonatal death rates decreased steadily from 24 weeks and reached a nadir at 36 weeks. Based on the risks of stillbirth and neonatal death, delivery of diamniotic monochorionic twins should be considered at 36 weeks, and delivery at 38 weeks should be considered for dichorionic twins.